2005
DOI: 10.1111/j.1467-9507.2005.00288.x
|View full text |Cite
|
Sign up to set email alerts
|

The Social Context of Young Children's Peer Victimization

Abstract: The goal of this study was to investigate differences in the social context of peer victimization for preschoolers and kindergarteners. Data were collected from 168 children. For preschoolers, neither social acceptance nor friendships were significantly related to peer victimization. Instead, playing with peers and exposure to aggressive peers were associated with higher rates of peer victimization. For kindergarteners, exposure to aggressive peers also contributed to the risk for peer victimization, but being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 55 publications
4
33
0
2
Order By: Relevance
“…Consistent with past research on peer victimization in younger children (4 -6 years of age) (Hanish, Ryan, Martin, & Fabes, 2005;Kochenderfer & Ladd, 1996b;Monks, Smith, & Swettenham, 2003;Perry, Kusel, & Perry, 1988), we defined victimization as a form of peer abuse in which a child is frequently the recipient of aggressive acts. These aggressive acts can be expressed both directly (e.g., hitting, calling names) and indirectly (e.g., isolation from the group, rumor spreading) (Alsaker & Valkanover, 2001;Crick, Casas, & Ku, 1999;Kochenderfer & Ladd, 1996a).…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…Consistent with past research on peer victimization in younger children (4 -6 years of age) (Hanish, Ryan, Martin, & Fabes, 2005;Kochenderfer & Ladd, 1996b;Monks, Smith, & Swettenham, 2003;Perry, Kusel, & Perry, 1988), we defined victimization as a form of peer abuse in which a child is frequently the recipient of aggressive acts. These aggressive acts can be expressed both directly (e.g., hitting, calling names) and indirectly (e.g., isolation from the group, rumor spreading) (Alsaker & Valkanover, 2001;Crick, Casas, & Ku, 1999;Kochenderfer & Ladd, 1996a).…”
mentioning
confidence: 58%
“…Consequently, these children were surrounded by a large group of peers of the same age. As found in several studies (e.g., Alsaker & Valkanover, 2001;Kochenderfer & Ladd, 1996b), not only is peer victimization a common occurrence during this age period, but this is also an age at which aggression toward peers peaks as well (Hanish et al, 2005). Given the fact that girls and boys play in separate groups, it can be argued that boys in large schools will be more exposed to aggressive behavior that, in turn, may increase the likelihood of becoming victimized.…”
Section: Discussionmentioning
confidence: 89%
“…The reciprocal friends of victims were also less well-adjusted socially than the friends of either bully-victims or non-involved adolescents. Hanish et al (2005) found that (a) being part of an aggressive peer group was positively related to victimization in kindergarteners and (b) both peer acceptance and the presence of friends were negatively related to victimization. Furthermore, those with emotional/behavioral regulation difficulties are at heightened risk for becoming victims who are also aggressive (Pellegrini et al 1999;Schwartz et al 2001).…”
Section: Victimizationmentioning
confidence: 96%
“…Disagreement exists in the field regarding the concept of bullying associated with kindergarten children and the kindergarten context, with a particular critical question concerning children's intentional actions (Hanish et al 2004;Kochenderfer and Ladd 1997).…”
Section: Introductionmentioning
confidence: 99%